Methadone Maintenance and HIV Prevention: A Cost-Effectiveness Analysis - Zaric, Gregory S.; Brandeau, Margaret L.; Barnett, Paul G. (Management Science, 2000)
We assess the cost-effectiveness of maintenance treatment for heroin addiction, with emphasis on its role in preventing HIV infection. The analysis is based on a dynamic compartmental model of the HIV epidemic among a population of adults, ages 18 to 44. The population is divided into nine compartments according to infection status and risk group. The model takes into account disease transmission from drug injection and sexual contacts. The health benefits of methadone maintenance and the resulting HIV infections averted are measured in terms of life years gained and quality-adjusted life years gained. Costs considered include all health-care costs (including cost of HIV care and other health care) and the cost of methadone maintenance. The analysis shows that expanding existing methadone maintenance programs is a cost-effective health-care intervention that can play an important role in slowing the spread of HIV and improving the length and quality of life for injection drug users (IDUs), and that such expansion is cost-effective even in populations with low HIV prevalence among IDUs. Incremental expansion of methadone maintenance programs was found to have a cost-effectiveness ratio of between $9,700 and $17,200 per life year gained, and between $6,300 and $10,900 per quality-adjusted life year gained. Although methadone maintenance treatment is provided to IDUs, the analysis shows that significant benefits accrue to non-IDU members of the population. Sensitivity analysis shows that new methadone maintenance treatment slots will be cost-effective even if they are twice as expensive and half as effective in reducing risky behavior as current methadone maintenance programs.